Integrating ecumenism and interreligious dialogue in peace education in the Philippines from a Catholic perspective - Gozum, Ivan Efreaim A (International journal of Christianity & education, 2023)
This study presents the importance of promoting interreligious dialogue and ecumenism in teaching peace education. It also discusses the applicability of selected papal documents for implementation in current interreligious education in Catholic and government schools in the Philippines. We explain the importance of interreligious dialogue and ecumenism from the Catholic Church documents Ut Unum Sint and Nostra Aetate. Then, we show the need for interreligious dialogue and ecumenism in achieving peace in this time when religion is misconstrued. Conclusions are given to lay out the need for interreligious dialogue and ecumenism to be integrated in peace education.